The administrative employees' perception towards corporate social responsibility and job satisfaction in Universiti Malaysia Kelantan (UMK) / Nornadirah Izzety Nordin - Nordin, Nornadirah Izzety (Faculty of Business Management, 2018)
This research aims to study the The Administrative Employees' Perceptive Towards Corporate Social Responsibility and Job Satisfaction at Universiti Malaysia Kelantan (UMK). The limitations of the study were focused on the employees in UMK. The questionnaire was distributed to 80 respondents in UMK. The components in the CSR play an important roles towards employees perception about CSR which is it was give an impact on the employees either positive or negative outcome. On this study, it was focus two variables of CSR which are physical and behavioural components and level of job satisfaction. In the physical and behavioural components it was consist economic, legal, ethical, philanthropic, charity, stewardship and environmental. In this physical and behavioural component there was positive outcome. It was strong relationship between components of CSR and level of job satisfaction.